2022
DOI: 10.1007/s40200-022-01002-6
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of SARS-CoV-2 mutations and their impact on vaccination efficacy: an overview

Abstract: With the unexpected emergence of the novel 2019 Wuhan coronavirus, the world was faced with a sudden uproar that quickly shifted into a serious life-threatening pandemic. Affecting the lives of the global population and leaving drastic damage in various sections and systems, several measures have been constantly taken to tackle down this crisis. For instance, numerous vaccines have been developed in the past two years, some of which have been granted emergency use, thus providing sufficient immunity to the vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 163 publications
0
3
0
Order By: Relevance
“…The emerging SARS-CoV-2 variants such as Delta, Omicron, and its lineages (variants of concern, VOCs) have been found to cause significant adverse impacts by overpowering protective immunity induced by COVID-19 vaccines and antibody-based therapies, resulting in vaccine breakthrough infection, re-infection, and overall surging of cases and deaths amid different waves of the ongoing pandemic. Therefore, efforts are being made to develop more effective vaccines including variant-specific, mutation proof, universal nextgeneration vaccines, as well as administering more doses of vaccines (booster shots) for boosting protective immunity to safeguard health amid emerging variants [9][10][11][12][13][14][15]. Despite the development of few vaccines and the ongoing global vaccination drive, COVID-19 vaccination hesitancy, diplomacy, and inequitable access to vaccines, particularly among low-and middle-income countries, also constitute significant reasons for some hindrances in the ongoing global vaccination drive, including booster shots, which helped in the sustained global burden of COVID-19; hence, global vaccination coverage needs to be enhanced holistically [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The emerging SARS-CoV-2 variants such as Delta, Omicron, and its lineages (variants of concern, VOCs) have been found to cause significant adverse impacts by overpowering protective immunity induced by COVID-19 vaccines and antibody-based therapies, resulting in vaccine breakthrough infection, re-infection, and overall surging of cases and deaths amid different waves of the ongoing pandemic. Therefore, efforts are being made to develop more effective vaccines including variant-specific, mutation proof, universal nextgeneration vaccines, as well as administering more doses of vaccines (booster shots) for boosting protective immunity to safeguard health amid emerging variants [9][10][11][12][13][14][15]. Despite the development of few vaccines and the ongoing global vaccination drive, COVID-19 vaccination hesitancy, diplomacy, and inequitable access to vaccines, particularly among low-and middle-income countries, also constitute significant reasons for some hindrances in the ongoing global vaccination drive, including booster shots, which helped in the sustained global burden of COVID-19; hence, global vaccination coverage needs to be enhanced holistically [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The most critical structures of the NTD involve loops N3 and N5. They define a conformational epitope responsible for viral immune escape [ 46 ]. Regions 2, 5, and 6 of the NTD region correspond to loops N2, N3, and N4, as originally defined by Chi et al (2020) [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Initial statements indicated that the pooled efficacy of ChAdOx1-S against moderate or severe illness was 85%, while BBV152’s efficacy against severe COVID-19 was 93.4% [ 5 6 ]. However, the recurrent mutations of SARS-CoV-2 variants raise concerns about the vaccines’ effectiveness against COVID-19, with evidence suggesting reduced efficacy against certain mutated strains [ 7 8 ]. For example, against the Delta variant of SARS-CoV-2 (B.1.617.2), the effectiveness of the BBV152 vaccine and the ChAdOx1 vaccine was only 65.2% and 70.4%, respectively [ 9 10 ].…”
Section: Introductionmentioning
confidence: 99%